Employee Brand Equity Content Analysis on TikTok @nadalasido as Employee Generated Content of PT Paragon: Analisis Konten Ekuitas Merek Karyawan di TikTok @nadalasido sebagai Konten yang Dihasilkan Karyawan PT Paragon - Athaya Fairuzawa; Deslia, Iva Fikrani (Kanal: Jurnal Ilmu Komunikasi, 2026)
Digital developments lead companies to continuously innovate regarding promotions and corporate image to reach a wider audience. This study aims to determine the formation of Employee Brand Equity through Employee Generated Content using the @nadalasido account as a representation of PT Paragon’s employee creators. The research method uses qualitative with descriptive content analysis methods, with primary data sources taken directly from @nadalasido’s Tiktok videos related to the concepts of EBE and EGC. Data collection is carried out through documentation and tested through theory triangulation. The analysis of this study indicates that brand value representation can be formed naturally through employee’s digital expressions on personal accounts. The most prominent EBE element is Brand Consistent Behaviour, evident in consistent behaviour, visuals, and narratives that reflect PT Paragon’s value of professionalism, collaboration, and positive culture. Brand llegiance emerges through expressions of pride and enjoyable work experience, while Brand Endorsement emerges through of appearance of company products in everyday contexts without direct promotion. These findings demonstrate that employee creator can act as effective brand communicators. Thus, EGC contributes to strengthening EBE and helps build PT Paragons’s brand image in the digital space, particularly through TikTok.